The Anti-Corruption Campaign and the Inter-Generational Transmission of Working in Bureaucracy: Evidence from China - Shuai Chen; Erqi Ge (Global Labor Organization (GLO), 2024)
There is a clear and persistent inequality of bureaucratic employment between individuals with bureaucrat parents and those without. Using the recent anti-corruption campaign in China as a quasi-experiment, we investigate how counter-corruption endeavors affect inequality in bureaucratic employment through the inter-generational transmission of occupations. We conduct a difference-in-differences analysis to compare changes in the probability of working in bureaucracy after the campaign came into effect in different provincial administrative divisions of China, between individuals with a bureaucrat parent and those without. We find that before the campaign, bureaucrats' children were over 13 percentage points more likely to work in bureaucracy. However, after the campaign took effect, this premium significantly reduced by over 5 percentage points. Moreover, we explore potential mechanisms suggesting relatively better outside options for bureaucrats' children as a channel, while rejecting insider information of bureaucrat parents about the campaign, risk precaution or concern of bureaucrats' children, or changes in perceptions of bureaucracy among bureaucrats' children as alternative explanations.
Keywords: D73; H83; O12; P35; D63; 330; Anti-corruption; Bureaucracy; Inter-generational transmission; Inequality